Strength of Evidence of Electronic Media (Teleconference) In The Criminal Justice System - Mamulai, Muslim; Hardianto Djanggih; Mirnawanti Wahab (STAI Miftahul Ula Nganjuk, 2025)
The strength of the evidence of Electronic Media (teleconference) in the process of proving a criminal case according to the Criminal, specify a limited manner valid evidence and procedures for the use of that evidence thus have legal power of proof. Proof via electronic media (teleconference) regulates the judge / magistrate constitutional obligation to seek and find the truth so that the material taken into consideration for the judges in deciding a case. Implementation of evidence through electronic media in a criminal act, should the judge may use the priority when it will use the values ​​of the basic purpose of the law (justice, expediency and certainty) to accommodate the evidence through electronic media in examining the crime of existing.